LOYALTY PROGRAMS IN HOSPITALITY ON THE EXAMPLE OF HOTEL HOLIDAY INN SUSCHEVSKY - Tošić, Violeta; Tucović, Miloš; Tošić, Teodora (The Business of Tourism, 2021)
This paper will present one of the basic aspects of the formation of constant priorities of the company — customer loyalty, on the example of the hotel market in the Russian Federation. The hotel market in the Russian Federation is a developing segment with noticeable growth potential. This fact is confirmed by the increased number of investments through the appearance on the market of large international hotel chains such as The Rezidor Hotel Group, InterContinental Hotels Group, Marriott International.Research, analysis and constant work on achieving consumer loyalty is an important topic among marketers. More specifically, the topic of loyalty programs that enable companies regular consumers, and thus the growth and development of their company, is very current. Accordingly, a topic was chosen that represents such analysis in a completely different, non-competitive market for us, which can bring interesting and important examples and conclusions that can be implemented.
Keywords: costumer loyalty; loyalty programs; hotel market